Barriers and opportunities of the circular economy in small and medium enterprises: a systematic review of the literature - Fontoura, Daiane Gonçalves da; Bonato, Samuel Vinícius; Junges, Vanessa de Campos; Rodrigues, Guilherme de Oliveira; Salomão, Catherine Santos (Revista de Administração da UFSM, 2024)
This study aimed to present a portrait of studies on Circular Economy (CE) in Small and Medium-sized Companies (SMEs), from 2011 to 2021, referring to articles published in Scopus database journals. To this end, a systematic literature review (RSL) was developed, which collected a sample of 141 articles, which, after being evaluated, resulted in a total of 25 studies to be investigated, falling within the scope of this proposal. The main results show that the connections between the subjects are increasing, confirming that the implementation of CE aimed at SMEs has become a relevant issue that requires scientific deepening. There is a greater incidence of economic and political barriers, emphasizing the lack of financial resources combined with the lack of incentives for industries. The research contributes by exploring the concept of CE, taking into account current discussions on the subject. It is important that the barriers that inhibit the application of CE are overcome, that a model is properly designed and joint and strategic actions are implemented. The suggestion for future research involves the creation of a theoretical framework that articulates the identified elements and serves as a basis for SMEs, translating the transition as a path of sustainable organizational growth.